2020
DOI: 10.1152/ajpcell.00313.2019
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species-dependent regulation of pyruvate dehydrogenase kinase-4 in white adipose tissue

Abstract: Reactive oxygen species (ROS) are important signaling molecules mediating the exercise-induced adaptations in skeletal muscle. Acute exercise also drives the expression of genes involved in reesterification and glyceroneogenesis in white adipose tissue (WAT), but whether ROS play any role in this effect has not been explored. We speculated that exercise-induced ROS would regulate acute exercise-induced responses in WAT. To address this question, we utilized various models to alter redox signaling in WAT. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
2
11
1
Order By: Relevance
“…ROS can modulate intracellular signaling and a transient increase in ROS levels can promote adipocyte differentiation (38,43), while sustained elevation of cellular ROS levels has been linked to adipocyte lipid storage (24), also observed in microorganisms (44). Our data shows a clear positive relationship between ROS levels and lipid accumulation in contrast to a recent study in mice, where increased mitochondrial levels of the H2O2 hydrolyzing enzyme catalase were associated with reduced ROS, increased adiposity,adipocyte size and adipose glyceroneogenic and lipogenic gene expression (45). Another study also found reduced body weight with increased ROS levels in AT with aging (46).…”
Section: Discussioncontrasting
confidence: 75%
“…ROS can modulate intracellular signaling and a transient increase in ROS levels can promote adipocyte differentiation (38,43), while sustained elevation of cellular ROS levels has been linked to adipocyte lipid storage (24), also observed in microorganisms (44). Our data shows a clear positive relationship between ROS levels and lipid accumulation in contrast to a recent study in mice, where increased mitochondrial levels of the H2O2 hydrolyzing enzyme catalase were associated with reduced ROS, increased adiposity,adipocyte size and adipose glyceroneogenic and lipogenic gene expression (45). Another study also found reduced body weight with increased ROS levels in AT with aging (46).…”
Section: Discussioncontrasting
confidence: 75%
“…Loss of Cisd2 causes metabolic defects in patients with Wolfram syn-drome by blunting mitochondrial biogenesis, adipogenesis, insulin-stimulated glucose uptake and the secretion of adiponectin [ 140 , 152 ]. In white adipose tissues, adrenergic stimulation activates PDK4 [ 153 ] which has recently been implicated in MAM formation [ 104 ].…”
Section: Mam In the Regulation Of Insulin Sensitivity And Energy Homeostasismentioning
confidence: 99%
“…Indeed, inhibition of nicotinamide adenine dinucleotide phosphate oxidase‐mediated reactive oxygen species eliminates exercise‐induced protection against myocardial infarcts in rats (16) and decreases exercise‐stimulated glucose uptake in muscle (17). Conversely, mice overexpressing mitochondrial catalase have impaired exercise‐induced regulation of pyruvate dehydrogenase kinase in AT (18). These “hormetic‐like” features of exercise are likely driven by the upregulation of adaptive or counteractive signaling cascades that oppose inflammatory signaling and quickly restore cells, tissues, or organs to new homeostatic set points (e.g., exercise training adaptations).…”
Section: At Remodeling In Obesitymentioning
confidence: 99%